2005
DOI: 10.1136/jnnp.2003.026757
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome after epilepsy surgery in patients with normal preoperative MRI

Abstract: Objective: To determine outcome after epilepsy surgery in patients with normal preoperative magnetic resonance imaging (MRI). Methods: 24 adult and paediatric patients with normal preoperative MRIs were studied. They underwent epilepsy surgery between 1994 and 2001 and had at least one year of follow up. Results: At the most recent follow up, nine patients (37%) were seizure-free and 18 (75%) had at least a 90% reduction in seizure frequency with weekly or monthly seizures. Seizure freedom was not significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
3
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(154 citation statements)
references
References 29 publications
8
140
3
2
Order By: Relevance
“…This suggests that frontal drug-resistant partial epilepsy with normal MR imaging findings should raise the suspicion of type 2 FCD, and this is supported by surgical series of cryptogenic partial epilepsy, in which up to 40% of the resected cortical specimens (especially in the frontal lobe) corresponded to type 2 FCD at histology. 9,31,32 Moreover, a recent report of the International League against Epilepsy noted that none of the children with epilepsy diagnosed with tumor or ischemia had normal MR imaging findings. 11 Our study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that frontal drug-resistant partial epilepsy with normal MR imaging findings should raise the suspicion of type 2 FCD, and this is supported by surgical series of cryptogenic partial epilepsy, in which up to 40% of the resected cortical specimens (especially in the frontal lobe) corresponded to type 2 FCD at histology. 9,31,32 Moreover, a recent report of the International League against Epilepsy noted that none of the children with epilepsy diagnosed with tumor or ischemia had normal MR imaging findings. 11 Our study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…10,13,14,25 A number of studies have analyzed clinical characteristics and seizure outcome after temporal lobectomy in patients with MRI-negative TLE, although most of these have included patients with heterogeneous semiology, EEG, and memory scores. [6][7][8]11,15,21,23,32,35 In general, these investigations have documented inferior results after temporal lobectomy compared with mesial temporal sclerosis. Studies using intracranial recordings have demonstrated that the epileptogenic zone can lie exclusively within the mesial temporal lobe even when MRI results are completely normal.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]11,15,21,23,32,35 In addition, memory loss is often present in TLE, and material-specific memory deficits are highly specific to indicate laterality of TLE. 4,9 Therefore, it might be expected that the absence of MRI abnormalities and memory deficits would suggest an extramesial or extratemporal source of the seizures, even when the ictal semiology and the video electroencephalography (EEG) results are typical of TLE.…”
mentioning
confidence: 99%
“…Chapman, et al, 9 have described outcomes for 24 patients who had intractable seizures and normal MR imaging findings. In 42% of these patients, FCD was found.…”
Section: Neurosurg Focus / Volume 20 / January 2006mentioning
confidence: 99%